Pencegahan Perilaku Plagiasi Melalui Pendidikan Fikih Jurnalistik Bagi Mahasantri di Media Sosial - Ahmad Zarkasyi (Southeast Asian Journal of Islamic Education Management, 2022)
The demand for article publication among students has intensified in various universities. However, these demands lead to plagiarism behavior, so journalistic ethics education at the beginning of college entry needs to be socialized early. This research is the result of field research. Analysis of research data from interviews, observations, and documentation with the reduction, display, and verification stages. Journalistic fiqh, as the ethical basis for students of the Miftahul Ulum Lumajang Syari'ah College of Sciences, carries out ethical principles based on Islamic teachings; among others, in carrying out journalistic duties and publishing articles, they should convey information based on facts that can be confirmed, because if they manipulate research results It is the same as guarding against spreading false news or hoaxes, so that provoked parties to appear, and more importantly, not accessing pornographic websites and not using social media to sell prohibited items.   Keywords : learning, ethical, journalistic values, students